The integrated smart system to assist elderly at home - Wicaksono, Handy; Santoso, Petrus; Sugiarto, Indar; Gondowardoyo, Sean; Wijaya, Andrew; Halim, Jason; Hafizah Kamarudin, Nazhatul (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Some elders prefer to live independently rather than in a nursing home. However, they need to be assisted because of health and safety reasons. We developed an integrated system consisting of a smart home, a mobile robot, and a wearable device, using message queuing telemetry transport (MQTT) protocol to communicate with each other. The smart home can be monitored and controlled via a mobile application. We use the telepresence robot equipped with a light detection and ranging (LIDAR) sensor to perform simultaneous localization and mapping (SLAM) and autonomous navigation. The wearable device application is used to detect older adults' heart rate, the steps taken, and the burnt calories. We also add pose detection and location estimation using a depth camera powered by an efficient deep-learning algorithm. We also developed an Android application as a dashboard that monitors and controls all system components. Our system can facilitate communication between its various components.